Kemungkiran pemaju dalam produk pembiayaan perumahan secara Islam: Analisis pendekatan penyelesaian - Shuib, Mohd Sollehudin; Mohamad, Mohamad Taqiuddin; Sulaiman, Ahmad Azam (UKM Press, 2013)
As of the end of 2010, banks that offer Islamic home financing products in Malaysia have diversified the use of muamalat contracts in offering their home financing products.The contracts include Bay ‘Bithaman Ajil (BBA), Murabahah, Musharakah Mutanaqisah, and Istisna`. More than 10 banks still use the BBA contract while others begin to focus on the use of equity-based financing contracts such as Musharakah Mutanaqisah. In Malaysia, sales of a house can take place even before the house is built or when it is still under construction. Therefore, Islamic home financing products must be offered through an appropriate contract to ensure they encompass fair and compassionate elements consistent with the Islamic rules.Selection of a proper contract is crucial to circumvent the stigma that Islamic banking is unjust in cases of abandoned houses. Hence, this article tries to see how this problem is addressed specifically in four Islamic products;Bay ‘Bithaman Ajil (BBA), Murabahah, Musharakah Mutanaqisah, and Istisna’.In its analysis, this study applies three methods; inductive, deductive and comparative methods. The results show that certain contracts are better than others in protecting customers from directly assuming the burden in cases of abandoned houses.